Large-scale IPM validation in whitefly (Bemisia tabaci)-prone cotton (Gossypium spp.) fields adjoining kinnow orchards - KUMAR, ANOOP; BIRAH, AJANTA; TANWAR, R K; KHOKHAR, M K; SINGH, S P (The Indian Journal of Agricultural Sciences, 2023)
Whitefly [Bemisia tabaci (Gen)] is a serious sucking pest of cotton in the north zone of India. Cotton (Gossypium spp.) fields adjoining kinnow orchards used to have a quite higher incidence of whiteflies compared to the fields away from orchards. Therefore, the study was carried out at ICAR-National Centre for Integrated Pest Management, New Delhi during 2017–19 to implement integrated pest management (IPM) validation trial in cotton fields located adjoining the kinnow orchards in the village Nihalkhera of district Fazilka, Punjab in farmers’ participatory (FP). The IPM strategy consists of weed removal from orchards, timely sowing of recommended cotton hybrid, 4 foliar sprays of 2% potassium nitrate, use of azadirachtin 1500 ppm @5 ml/litre, conservation of natural enemies by avoidance of insecticides that are harmful (IOBC Class-4) to natural enemies and judicious use of safer pesticides (IOBC class1 and 2). The IPM adoption resulted in the successful management of whitefly and other sucking pests along with a two to three-fold increase in predator population compared to FP. IPM recorded a substantial reduction in the use of pesticide active ingredients (86%) and the number of sprays (58%) along with high parasitization (35.32–45.98%) of whitefly nymphs by Encarsia sp. IPM provided a significant increase in yield (23%), net return (57.5%) along with a high benefit cost (B:C) ratio of 2.65.